Zajścia antyżydowskie na Lubelszczyźnie w pierwszych latach po drugiej wojnie światowej - Kopciowski, Adam (Zagłada Żydów. Studia i Materiały, 2007)
In the early years following World War II, the Lublin region was one of the most important centres of Jewish life. At the same time, during 19441946 it was the scene of anti-Jewish incidents: from anti-Semitic propaganda, accusation of ritual murder, economic boycott, to cases of individual or collective murder. The wave of anti-Jewish that lasted until autumn of 1946 resulted in a lengthy and, no doubt incomplete, list of 118 murdered Jews. Escalating anti-Jewish violence in the immediate post-war years was one of the main factors, albeit not the only one, to affect the demography (mass emigration) and the socio-political condition of the Jewish population in the Lublin region